2015
DOI: 10.1002/hyp.10489
|View full text |Cite
|
Sign up to set email alerts
|

Using equilibrium temperature to assess thermal disturbances in rivers

Abstract: Flow regulation is widely known to modify the thermal regime of rivers. Here, we examine the sensitivity of an empirical approach, the Equilibrium Temperature Concept (ETC), to detect both the effects of hydraulic infrastructures on the annual thermal cycle and the recovery of the thermal equilibrium with the atmosphere. Analysis was undertaken in a Pyrenean river (the Noguera Pallaresa, Ebro basin) affected by a series of reservoirs and hydropower plants. Equilibrium temperature (Te) is defined as the water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
2
5
0
1
Order By: Relevance
“…As already reported by Buendia et al [28] the annual water yield of the whole catchment averages 1330 hm 3 /year (1 hm 3 = 1 × 10 6 m 3 ) with May and June concentrated most of it (180 hm 3 and 260 hm 3 , respectively), typically due to snowmelt. The flow regime of the river has been altered by dams that were built up along the 20th century for hydropower production.…”
Section: The Basinsupporting
confidence: 64%
See 1 more Smart Citation
“…As already reported by Buendia et al [28] the annual water yield of the whole catchment averages 1330 hm 3 /year (1 hm 3 = 1 × 10 6 m 3 ) with May and June concentrated most of it (180 hm 3 and 260 hm 3 , respectively), typically due to snowmelt. The flow regime of the river has been altered by dams that were built up along the 20th century for hydropower production.…”
Section: The Basinsupporting
confidence: 64%
“…Mean annual temperature ranges from 4 °C at the headwaters to 14 °C in the lowlands. Most of the catchment area (83%) is covered by forests and grassland, 9% is occupied by agriculture (located in lowlands and valley bottoms), while the remaining 8% belong to small villages and rocky outcrops [28,29].…”
Section: The Basinmentioning
confidence: 99%
“…Indeed, water temperature downstream of the two storage dams was less responsive to ambient meteorological conditions as demonstrated by the weak correlation between air and water temperature residuals (Table ). A similar decoupling between water temperature and atmospheric conditions was also observed downstream of dams in the Ebro basin, Spain (Buendía et al, ). Moreover, findings from the present study are consistent with the study by Steel and Lange () who also observed a reduction in water temperature variability at short temporal scales (1 to 8 days) downstream of hypolimnetic‐release dams in the Willamette basin, Oregon.…”
Section: Discussionsupporting
confidence: 65%
“…In the case of the St‐Jean River, the increase in net incoming solar radiation as a result of the small impoundment (reservoir area = 6 ha and storage capacity = 0.3 × 10 6 m 3 ; Table ) upstream of the dam was likely insufficient to significantly warm the regulated river. Recent studies suggest that the volume of the impoundment should be considered in conjunction with the size of the river when assessing thermal alteration by dams (Buendía et al, ; Maheu, ). For example, the ratio of reservoir maximum storage capacity (m 3 ) to median annual runoff (m 3 ), a useful indicator to assess the potential for hydrological and thermal alteration by dams (Batalla et al, ), was smaller than 0.1% for the run‐of‐river dam assessed in the present study (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation